Adoptive T‐cell therapy for fungal infections in haematology patients. Issue 8 (14th August 2015) - Deo, Shivashni S; Gottlieb, David J
Abstract : The prolonged immune deficiency resulting from haematopoietic stem cell transplant and chemotherapy predisposes to a high risk of invasive fungal infections. Despite the recent advances in molecular diagnostic testing, early initiation of pre‐emptive antifungal therapy and the use of combination pharmacotherapy, mortality from invasive mould infections remain high among recipients of allogeneic stem cell transplant. The increasing incidences of previously rare and drug‐resistant strains of fungi present a further clinical challenge. Therefore, there is a need for novel strategies to combat fungal infections in the immunocompromised. Adoptive therapy using in vitro ‐expanded fungus‐specific CD4 cells of the Th‐1 type has shown clinical efficacy in murine studies and in a small human clinical study. Several techniques for the isolation and expansion of fungus‐specific T cells have been successfully applied. Here we discuss the incidence and changing patterns of invasive fungal diseases, clinical evidence supporting the role of T cells in fungal immunity, methods to expand fungus‐specific T cells in the laboratory and considerations surrounding the use of T cells for fungal immunotherapy.